On-farm management and quality assessment of farmers’ saved wheat seed in the western Terai, Nepal (Agronomy Journal of Nepal, 2013)
A study was conducted at Pakadi Village of Kapilbastu district, western Terai, Nepal in 2005 to find out the effect of on-farm seed management on the quality status of farmers’ saved wheat seed. A survey was conducted to collect required information about on-farm seed management by using pre-tested questionnaires as well as to collect wheat seed samples, which were produced under general, additional and standard management practices. Survey showed that most of the farmers fulfilled their seed demand through informal sources. Roguing was not common practices in the study site and majority of the farmers saved seed from the harvest which was used for consumption purpose as well. Also, majority of farmers used to store unknown quality of seed in local containers by adopting simple storage techniques, which were one of the major causes of seed deterioration in their condition. Except physical purity, other seed quality attributes such as germination, 1000 seed weight and genetic purity percentage were found highest in certified seed. However, vital seed quality attribute viz. germination percentage of certified seed produced under standard management practice was statistically at par with seed produced under additional management practice. Likewise, other crop mixed seed, varietal mixing; and percentage infection of diseases such as Bipolaris sorokiniana and Alternaria spp. were found minimum in certified seed produced under standard management, while those attributes were recorded in high amount for seed produced under general and additional management followed by farmers. It showed that on-farm seed management played a significant role for maintaining seed quality parameters except physical purity and weed mixture in the seed. It was concluded that high quality wheat seed could be produced under farmers' condition by adopting additional management system with treatment and processing of seed. DOI: http://dx.doi.org/10.3126/ajn.v1i0.7542 Agronomy Journal of Nepal (Agron JN) Vol. 1: 2010 pp.50-60